Penerapan Lean Manufacturing Menggunakan Metode Waste Assessment Model (WAM) Untuk Mengurangi Waste Pada Lini Produksi Steel Structure - Faisal Afriandi; Joumil Aidil Saifuddin (Pusat Riset dan Inovasi Nasional, 2023)
PT Gerbang Saranabaja is a company engaged in the steel fabrication and construction industry. The type of Engineer-to-order request in the production process causes the products produced to have their own characteristics and specifications according to client requests so that in the production process there is still waste caused by various factors. The purpose of this research is to identify critical waste with the Waste Assessment Model method, find out the root cause of critical waste with Root Cause Analyst and produce alternative recommendations for improvement with 5W + 1H Analysis in the production process at PT Gerbang Saranabaja. The results showed that the crisis waste in the production process was Motion with a final value of 0.00387, defect with a final value of 0.00354 and Inventory with a final value of 0.00345. The crisis waste that occurs is caused by various interrelated things and the alternative improvements that can be made are to improve team coordination in various aspects, evaluate and optimize the layout of the work area, increase awareness of work quality through training, review and improve production capacity planning and optimize line balancing in the production area.